Системы с направлением режущего инструмента в операционных системах с силовой головкой и насадкой - Бурдейная, Виктория Михайловна; Трищ, Андрей Романович; Доценко, Наталья Андреевна (НТУ "ХПИ", 2016)
В статье рассмотрена функциональная зависимость изменения полей рассеяния размеров от базы и позиционных отклонения осей. Получены статистические характеристики распределения от базовой поверхности до оси отверстия и расположения осей отверстий. Предложены зависимости для расчета полей рассеяния размера от базы и позиционного отклонения при обработке отверстий в системах с направлением режущего инструмента. Определен удельный вес влияния факторов на точность обработки координированных отверстий в системах с направлением режущего инструмента.

The article considers the functional dependence of the stray fields from the base size and position deviation of the axes. The purpose of a comprehensive study of the influence of various elements of technological equipment of modular machines (power heads, jigs and fixtures) to provide the normalized precision machining of holes coordinated with consideration of the positional deviations of their axes during machining and without guiding the cutting tool. The obtained statistical characteristics of the distribution from the base surface to the bore axisand the location of the axes of the holes. Checked the hypothesis about the adequacy of the presented results of research at F-criterionand t-criterion. The dependences for calculation of the stray fields from the base size and position deviation in the machining of holes in the systems with the direction of the cutting tool. Set change limits when using drill bushings with factors such as the length of a guide portion, the overhang over the end of the sleeve, the diameter of the tool, the hardness of the processed material. Determined the proportion of influence of factors on the machining accuracy of holes in the coordinate systems with the direction of the cutting tool. The obtained values of parameters of statistical analysis models in a coordinated drilling of holes nozzles with the conductors. Determined the total effect of controllable factors on the magnitude of the stray fields of size from the base to the axis of the hole and the positional deviation of the bore axis, giving a substantial reserve regulation precision machining coordinated holes. The change in diameters does not lead to a significant increase in stray field.
System with the direction of the cutting tool in operating systems with the power head and attachment
Keywords: точность; координированные отверстия; фактор; инструмент; coordinated holes; factor; tool